Exploring Risk Factors Affecting Sustainable Outcomes of Global Public–Private Partnership (PPP) Projects: A Stakeholder Perspective - Zilin Li; Haotian Wang (Buildings, 2023)
As a model for delivering infrastructure initiatives, public–private partnerships (PPPs) have gained significant popularity in recent years. The globalization of PPP has exposed them to elevated risks emanating from the international real economy and financial market, which can ultimately result in project cancellations or distress. This study analyzes risk factors affecting the sustainable outcomes of global PPP projects from a stakeholder perspective. After identifying the interests of key stakeholders and examining how various risks influence stakeholders’ interests, a two-step binomial probit model is used to investigate domestic and international risk factors in PPP arrangements based on the World Bank PPI database. The empirical results indicate that inflation has a substantially positive effect on project failure, while factors such as PPP experience, central government involvement, exchange rate fluctuations, etc., significantly contribute to PPP success. In addition, the study demonstrates that trade openness and net foreign direct investment (FDI) inflow are crucial for the transmission of global risks. The study also provides policy implications and recommendations from a risk allocation–stakeholder relationship perspective to enhance the resilience of PPP initiatives based on these findings.